Crystal Structure of Inorganic Pyrophosphatase From Schistosoma japonicum Reveals the Mechanism of Chemicals and Substrate Inhibition - Wu, Qun-Feng; Wang, Wei-Si; Chen, Shen-Bo; Xu, Bin; Li, Yong-Dong; Chen, Jun-Hu (Frontiers in Cell and Developmental Biology, 2021)
Soluble inorganic pyrophosphatases (PPases) are essential for facilitating the growth and development of organisms, making them attractive functional proteins. To provide insight into the molecular basis of PPases in Schistosoma japonicum (SjPPase), we expressed the recombinant SjPPase, analyzed the hydrolysis mechanism of inorganic pyrophosphate (PPi), and measured its activity. Moreover, we solved the crystal structure of SjPPase in complex with orthophosphate (Pi) and performed PPi and methylene diphosphonic acid (MDP) docking into the active site. Our results suggest that the SjPPase possesses PPi hydrolysis activity, and the activity declines with increased MDP or NaF concentration. However, the enzyme shows unexpected substrate inhibition properties. Through PPi metabolic pathway analysis, the physiological action of substrate inhibition might be energy saving, adaptably cytoprotective, and biosynthetic rate regulating. Furthermore, the structure of apo-SjPPase and SjPPase with Pi has been solved at 2.6 and 2.3 Å, respectively. The docking of PPi into the active site of the SjPPase-Pi complex revealed that substrate inhibition might result from blocking Pi exit due to excess PPi in the SjPPase-Pi complex of the catalytic cycle. Our results revealed the structural features of apo-SjPPase and the SjPPase-Pi complex by X-ray crystallography, providing novel insights into the physiological functions of PPase in S. japonicum without the PPi transporter and the mechanism of its substrate inhibition.